A review of the genus Prosodes Eschscholtz, 1829 (Coleoptera: Tenebrionidae) of Iran - Chigray, Ivan; Nabozhenko, Maxim; Merkl, Ottó; Kovalev, Alexey (Zootaxa, 2018)
A taxonomic review of the genus Prosodes Eschscholtz, 1829 of Iran is given. Two new species from the subgenus Meropersina Reitter, 1909 are described, both from West Azerbaijan Province: P. kasatkini sp. n. and P. shokhini sp. n. Three new synonymies are proposed: Prosodes (Dilopersina) mithras Reitter, 1904 = Prosodes (Dilopersina) chorassanica G. Medvedev, 1996, syn. n., Prosodes (Dilopersina) neopersis Semenov, 1910 = Prosodes (Dilopersina) exilis Medvedev, 1996, syn. n., Prosodes (Meropersina) cordicollis Allard, 1883 = P. cordicollis v. vermicularis Reitter, 1909, syn. n. Lectotypes are designated for Prosodes calcarata Reitter, 1893, Prosodes cordicollis v. vermicularis Reitter, 1909, Prosodes dentimana Reitter, 1909, Prosodes jakowlewi Reitter, 1909, Prosodes jakowlewi Semenov, 1894, Prosodes laticauda Reitter, 1896, Prosodes mithras Reitter, 1904, Prosodes vermiculosa Reitter, 1909, and Prosodes consanguinea Allard, 1885. The Iranian species Prosodes neopersis Semenov, 1910 is resurrected from the synonymy of Prosodes vestita Allard, 1880 and recorded from Turkmenistan for the first time. Prosodes vestita Allard, 1880 is raised to species level. The distribution of Prosodes kraatzi Reitter, 1893 is corrected: this species is known only from Eastern Afghanistan (not from Iran). Morphology of the two closely related subgenera, Dilopersina Reitter, 1909 and Meropersina Reitter, 1909 is discussed. A key to 17 Iranian species of the genus Prosodes is given (Prosodes kraatzi with doubtful Iranian occurrence is also added).